PENGARUH PERSONAL SELLING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ASURANSI PADA PT.AXA FINANCIAL MEDAN - Indri Wahyuni Saragih; Muhammad Aguung Anggoro (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research was conducted at PT.Axa Financial Medan. The purpose of this study is to test and analyze the influence of personal selling and product quality positively and significantly on buying decision insurance at PT.Axa Financial Medan. The research method used is multiple linear regression analysis. The population in the study were 128 customers and a sample of 102 customers. Sample testing techniques include sample random sampling. The result of the study show that partially the personal selling and the quality of product has a positive and significant effect on buying decision insurance at PT.Axa Financial Medan. Simultaneously Personal Selling and Product Quality have a positive and significant effect on buying decision insurance at PT.Axa Financial Medan. The magnitude of the coefficient of determination obtained Adjusted R Square value of 0,495 this means 49,5% of the dependent variable Buying Decision insurance at PT.Axa Financial Medan which can be explained by the independent variable Personal Selling and Product Quality while the remaining 50,5% is explained by other variables not examined in this study, such as company price, service quality, brand image and so on.